Duty, Pathology and the Problem of Intersubjectivity in the Late Philosophy of I. Kant - Putinaitė, Nerija (Problemos, 2001)
The paper reflects on the question of the status of intersubjectivity in the context of Kantian distinction between duty and pathology. Duty is shown to be the basis for the construction of moral and legal normativity and decisive for the description of an acting subject. The specificity of Kant’s moral, legal and political subject is discussed, and the consequences for an intersubjective relation and the community are drawn. The Kantian subject is found to be incorporated into the legal community, not as a constructing element of it. The paper raises a question of the normativity of legal and moral behaviour and asks whether it is possible to deal with the otherness of “the other” not as a mere pathology that has to be eliminated but also as a constructive element of the state. The question is raised: Does in every case intersubjectivity, as rooted in the otherness, have to be excluded from the sphere of ethics and law, as based on the rational normativity?